Semen proteomics reveals alterations in fertility-related proteins post-recovery from COVID-19 - Dash, Ankita; Salkar, Akanksha; Nissa, Mehar Un; Makwana, Prashant; Athalye, Arundhati; Parikh, Swapneil; Srivastava, Sanjeeva; Parikh, Firuza (Frontiers in Physiology, 2023)
Changes to sperm quality and decline in reproductive function have been reported in COVID-19-recovered males. Further, the emergence of SARS-CoV-2 variants has caused the resurgences of COVID-19 cases globally during the last two years. These variants show increased infectivity and transmission along with immune escape mechanisms, which threaten the already burdened healthcare system. However, whether COVID-19 variants induce an effect on the male reproductive system even after recovery remains elusive. We used mass-spectrometry-based proteomics approaches to understand the post-COVID-19 effect on reproductive health in men using semen samples post-recovery from COVID-19. The samples were collected between late 2020 (1 st wave, n=20), and early-to-mid 2021 (2 nd wave, n=21); control samples were included (n=10). During the 1 st wave alpha variant was prevalent in India, whereas the delta variant dominated the second wave. On comparing the COVID-19-recovered patients from the two waves with control samples, using one-way ANOVA, we identified 69 significantly dysregulated proteins among the three groups. Indeed, this was also reflected by the changes in sperm count, morphology, and motility of the COVID-19-recovered patients. In addition, the pathway enrichment analysis showed that the regulated exocytosis, neutrophil degranulation, antibacterial immune response, spermatogenesis, spermatid development, regulation of extracellular matrix organization, regulation of peptidase activity, and regulations of calcium ion transport were significantly dysregulated. These pathways directly or indirectly affect sperm parameters and function.Our study provides a comprehensive landscape of expression trends of semen proteins related to male fertility in men recovering from COVID-19. Our study suggests that the effect of COVID-19 on the male reproductive system persists even after recovery from COVID-19. In addition, these post-COVID-19 complications persist irrespective of the prevalent variants or vaccination status.